Hubungan Unsafe Action dan Unsafe Condition dengan Kecelakaan Kerja di PT X Padang - Anshari, Luthfil Hadi; Azkha, Nizwardi; Ernawati, Tuty (Jurnal Kesehatan Komunitas, 2025)
Unsafe actions are behaviors that can endanger workers or others and have the potential to cause workplace accidents. In addition, unsafe conditions in the work environment are also important factors that increase the risk of accidents. This study aims to determine the relationship between unsafe actions and unsafe conditions with the incidence of occupational accidents among workers at PT X in 2024. This research employed a quantitative method with a cross-sectional design. The sampling technique used was proportional random sampling. From a total population of 129 workers, 55 were selected as research samples. The study was conducted from March to September 2024 at PT X Padang. The results showed that 52.7% of respondents experienced workplace accidents, 52.7% performed unsafe actions, and 56.4% worked under unsafe conditions. The chi-square analysis indicated a significant relationship between unsafe actions and workplace accidents (p=0.001), as well as between unsafe conditions and workplace accidents (p=0.002). These findings confirm that unsafe behaviors and unsafe working conditions contribute to the occurrence of workplace accidents. Therefore, companies need to strengthen the implementation of Standard Operating Procedures (SOPs), enhance supervision and safety training, and encourage workers to consistently use Personal Protective Equipment (PPE) to prevent occupational accidents. Moreover, effective occupational safety management is essential to minimize the risk of workplace accidents.